Influência da laserterapia no desempenho, recuperação e no estresse oxidativo de corredores amadores - RODRIGUES, Lucas Ribeiro (2018)
ARTIGO 1: Objetctive: To analyze the lasertherapy effects on total running time, distance traveled and recovery on progressive incremental treadmill test until exhaustion. Methods: Participants visited the laboratory on two occasions and performed the same incremental treadmill test, with random interventions in a crossover design: laser or sham condition. Running time and distance traveled were recorded. Creatine kinase (CK) level, as well as subjective perceptions of recovery and pain were used as recovery measures. Pre and post differences in the variables, determined for both between and within conditions, were statistically tested using the Paired T-test for time running and distance traveled, ANOVA Two Way for CK activity, and for Subjective Perceptions of Recovery and Pain were used Wilcoxon non-parametric tests for a comparison within the groups and Mann Whitney for comparison between the groups. Results: Compared with the Sham condition, the lasertherapy applied immediately before the tests did not improve the running time (Δ = 23,66s vs. Δ = 31,33s), distance traveled (Δ = 0,12km vs. Δ = 0,14km), subjective perceptions of recovery (Δ = 0,5 vs. Δ = 0) and pain (Δ = 0,5 vs. Δ = 0) and CK activity (67,2 U/L vs. 135 U/L) in the 48-hours posttest. Conclusion: The results suggest that lasertherapy applied immediately before the treadmill test has no effect on running performance and subjective perceptions of pain and recovery. However, they showed lower increases in CK levels, especially at the post-x 24 hour time point. ARTIGO 2: Objetctive: To analyze the effects of lasertherapy on oxidative stress after a progressive incremental treadmill test. Methods: Twelve trained men participated in the study. The study visits were divided in two phases (two different weeks with three visits each) using the same test protocol, but with a random assignment to the interventions: laser or sham. Lipid peroxidation, total thiols, catalase (CAT) and superoxide dismutase (SOD) were used as measures of oxidative stress. Variables were compared using the ANOVA Two Way test. Results: Lasertherapy did not significantly improve the TBARS, total thiols values and was not able to modulate the activity of the CAT and SOD enzymes, post, 24 and 48 hours after the incremental treadmill test, compared to the Sham condition. Conclusion: The results suggest that the use of lasertherapy applied immediately before the aerobic treadmill test may decrease the increases in exercise-induced lipid peroxidation.